Sudanese journalists awarded UNESCO press freedom prize (UN News, 2026)
An independent organization for journalists in Sudan has been honoured for its commitment “to deliver accurate, lifesaving information” amid the ongoing civil war, the UN educational and cultural agency UNESCO announced.
Sudan